Anxiety sensitivity class membership moderates the effects of pre-quit reduction in anxiety sensitivity on quit-day tobacco craving. (April 2016) - Bakhshaie, Jafar; Zvolensky, Michael J.; Langdon, Kirsten J.; Leventhal, Adam M.; Smits, Jasper A.J.; Allan, Nicholas; Schmidt, Norman B.
Highlights: Anxiety sensitivity (AS) class moderates the effects of "pre-quit reduction" in AS. Among AS "high-risk class" smokers, lesser reduction in AS predicts greater craving. AS class is a clinically important factor in post-quit craving processes. Abstract: Background: Although anxiety sensitivity has been primarily conceptualized as a dimensional latent construct, empirical evidence suggests that it also maintains a latent class structure, reflecting low-, moderate-, and high-risk underlying classes. The present study sought to explore whether these anxiety sensitivity classes moderated the relations between the degree of pre-quit reductions in anxiety sensitivity and the severity of nicotine withdrawal symptoms and craving experienced on quit-day. Methods: Participants included 195 adult smokers (47% female; Mage = 39.4) participating in a larger "anxiety sensitivity reduction-smoking cessation" intervention trial. Results: Anxiety sensitivity class significantly moderated relations between pre-quit reduction in anxiety sensitivity and quit-day craving. Specifically, smokers within the anxiety sensitivity high-risk class, who also demonstrated lesser pre-quit reductions in anxiety sensitivity, experienced the highest levels of craving on quit-day. Conclusions: These findings highlight the importance of 'high-risk' classes of anxiety sensitivity to better understand the experience of craving on quit day.